COVID-19 and health behaviors of the vulnerable group in the disaster-prone area:a case study of volcano-prone Merapi, Indonesia - Romi Bhakti Hartarto (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2022)
As the world’s fourth most populous country, Indonesia is predicted to suffer greatly from the pandemic. One of the most vulnerable groups in Indonesia is those living in the disaster-prone areas where access to health services is limited. This study aims to identify whether households in the disaster-prone area were already aware of and have implemented protective health behaviors during the COVID-19 pandemic. The location of the study was at Dongkelsari settlement houses in the Disaster-Prone Area III of Mount Merapi, the most active volcano in Indonesia. Descriptive statistics were used to summarize the quantitative data collected from face-to-face interviews with 142 out of 161 households residing in that area. Our findings suggest that knowledge about disease and prevention is quite high in our sample. More than 90% of the sample were already aware of COVID-19 transmission and understood that washing hands and wearing facemasks can prevent the spread of COVID-19. This high level of awareness is inseparable from the active role of community leaders in Dongkelsari area. However, only less than half of the sample reported practicing safe physical distancing. In conclusion, our study relies on field observation, and this complements the existing evidence by capturing a clearer picture of the COVID-19 awareness among the underrepresented population living in the disaster-prone area of Merapi volcano.